(untitled) (Advancements in Homeopathic Research, 2022)
Respiratory diseases are one of the most common burdens to look into the health care system worldwide. It is known that bronchial asthma, acute respiratory infections, chronic obstructive pulmonary disease, tuberculosis, and lung cancer are the five largest respiratory diseases which are global burden. Worldwide prevalence of Bronchial Asthma is estimated that around 235 million, among that South Asia is having higher affinity with an estimated one tenth of global bronchial asthma cases living in India.Bronchial asthma is one among the chronic inflammatory diseases having episodic or permanent symptoms and associated with variable airway obstruction. 3 It is greatly exacerbated by personality of patient, behaviors of patient and psychological factors like stress, habits, affective disorders and anxiety.